2023
DOI: 10.1055/a-2104-1520
|View full text |Cite
|
Sign up to set email alerts
|

The Enigma of Basilar Artery Dissections Secondary to Vasospasm following Subarachnoid Hemorrhage; Exploration of the Unknown Effect of Superior Cervical Ganglia: A Preliminary Experimental Study

Abstract: Background: Life-threatening basilar artery dissection (BAD) can be seen following subarachnoid hemorrhage (SAH), but it is not clear whether subarachnoid hemorrhage causes dissection, or not. This study aims to investigate the relationship between, degenerative changes in the superior cervical ganglia and the dissection rate of the basilar artery. Material and Method: In this article, after three weeks of experimental SAH, animals were decapitated. 18 rabbits were divided into three groups, according to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…SAH is a neurovascular condition associated with high morbidity and mortality (14), and NPE is one of the serious complication. The major underlying mechanism of NPE is sympathetic hyperactivity, but there might be other reasons and pathologies involved.…”
Section: Discussionmentioning
confidence: 99%
“…SAH is a neurovascular condition associated with high morbidity and mortality (14), and NPE is one of the serious complication. The major underlying mechanism of NPE is sympathetic hyperactivity, but there might be other reasons and pathologies involved.…”
Section: Discussionmentioning
confidence: 99%
“…8 Of particular significance is the fact that recent studies have reported the absence of hemorrhage, desquamation, or rupture within the intimal layer in subjects during the acute phase following SAH. [9][10][11][12] Nonetheless, during the experimental phase of a prior study, 13 an unexpected observation surfaced: a disruption in the integrity of the inner elastic membrane within a basilar artery sample, occurring after the acute period. However, since that was not the subject of the study, the authors only mentioned this finding and did not discuss it exclusively.…”
Section: Introductionmentioning
confidence: 99%